(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تعتبر شبكات الأسس في الحلقات من أحدث أصناف الشبكات، إذ تم الاهتمام بدراستها في أواخر التسعينات من القرن الماضي. الهدف من هذا البحث هو دراسة العلاقة بين شبكة الأسس في الحلقة وبين شبكة بول، ونهتم بشكل خاص بالسمات التي تتصف بها علاقة الترتيب في شبكة الأسس. ومن أهم النتائج إعطاء مثال على أن شبكات الأسس في الحلقات لا تشكل بالضرورة شبكات. The lattice of radicals ring is considered the most recent type of lattices, and has been studied since the nineties of the last century. The purpose of this article is to reveal the relationship between the lattice of radicals ring and Boolean lattice, specially the specific characteristics of the order relation in the Lattice of radicals. However, one of the most important conclusions is that giving examples shows that the lattices of radicals rings are not necessarily Boolean lattices, even if they were complete distributive lattice.